Experimental study of the heat transfer characteristics of a new-type flat micro-heat pipe thermal storage unit. (5th October 2015) - Diao, Y.H.; Wang, S.; Zhao, Y.H.; Zhu, T.T.; Li, C.Z.; Li, F.F.
Abstract: In this study, the heat transfer characteristics of a new-type flat micro-heat pipe thermal storage unit, which uses a moderate-temperature paraffin as heat storage phase change material, were investigated. The basic structure, working principle, and design concept of the thermal storage unit were discussed. Experiments were conducted to study the charging and discharging heat transfer processes of the thermal storage unit under different inlet temperatures and flow rates for the cold/hot heat transfer fluid (HTF). Experimental results show that the performance of the thermal storage unit was steady and efficient during heat charging and discharging, and the average charging and discharging powers of the thermal storage unit were approximately 658 and 894 W, respectively, under specific experimental parameters. Highlights: A thermal storage unit using new-type flat micro-heat pipes was presented. The performance of the thermal storage unit was investigated experimentally. The thermal storage unit has good performance in the charging/discharging process.